Microwave gasdischarge source of biologically active UV radiation and ozone as efficient means for sanitation of the indoor air. (November 2019) - Ivashkin, Pavel; Andreev, Sergey; Moryakov, Ivan; Ovsyankina, Alla; Rud', Ivan; Sevostyanov, Sergey; Savchenko, Ivan; Tsybulsky, Alexey; Denisov, Roman
Abstract: A new system of UV sanitization of the air environment in the premises of OVOD-1a, based on high-efficiency microwave gasdischarge lamps developed in GPI RAS, is described. The first experiments demonstrating the air purification capabilities of UV equipment were carried out. It is shown that in the laboratory premises used for the stay of livestock breeding in agriculture, the energy price of almost complete purification of the air from viral and fungal components is about η ≈ 10 −2 kW·h/m 3 . Bacterial sanitation of laboratory space is carried out with an energy cost of η ≈ 3·10 −2 kW·h/m 3 . The fundamental physical processes underlying microwave UV lamps, which are the main component of OVOD-1a sanitation system, are discussed.